Dysplastic consecutive patella dislocation (syndrome of patella disequilibrium) - I. G. Klimenko (Scientific Сentre for Family Health and Human Reproduction Problems, 2013)
The article presents the method of examination of patients with knee-joint pathology (consecutive slipping patella) that includes collection of anamnestic data, evaluation of state of the joint, complex X-ray examinationfor determination of patella-femoral congruence degree. In some questionable cases additional MR-image examination of joint is necessary. The most informative indices were: Blumensaat determination of line, lnsall - Salvati index, criteria of determination of patella height by Blackburne - Peel, criteria of vertical position of patella, angle of patella opening by Wiberg, angle of opening of femoral block of femoral bone by Ficat or sulcular angle, congruence angle by Merchant, lateral patella-femoral angle and less studied patella-femoral index.